The predictors of occupationally related injury in employees of Pasteur Institute of Iran - Rouzbeh Bashar; Korosh Holakoyee Nayini; Ramin Mehrdad; Maryam Fazeli; Masoumeh Arab; Nazanin Shabansalmani (Journal of Biology and Medicine - Peertechz Publications, 2023)
Background: Needlestick Injuries (NSI) are a critical occupational risk for healthcare workers. Therefore, the present study investigated the incidence and risk factors of NSI among employees of the Pasteur Institute of Iran, one of the largest and oldest biological research institutes in the country, who are at high risk of occupational exposure to biological agents. Methods: This cross-sectional study included all personnel (565 individuals) of the Pasteur Institute of Iran. Participants answered some questions related to demographic and occupational characteristics as well as occupational exposure to blood and biological products, and occupational protection.  Findings: A total of 448 questionnaires were completed. The mean age (SD) and work experience of the participants were 35.62 (9.20) and 9.72 (1.30) years, respectively. A total of 150 individuals had a history of NSI. The mean (SD) ages of participants with and without a history of NSV were 37.40 ± 9.03 and 34.41 ± 8.80 years, respectively (p < 0.001). The occurrence of NSI was related to work experience of more than five years and drinking, eating, or smoking while working. In addition, changing gloves while using the telephone was significantly related to reporting the occurrence of NSI to the department manager. Conclusion: Our findings indicated the relatively high frequency of NSI among the respondents. Despite the importance of personnel training, we did not find the occurrence of NSI or reporting it to be related to attending training courses. Hence, designing efficient preventive and protective measures requires the assessment of the attitudes of the mentioned institute's personnel toward NSI and its prevention and management.